Torsion of the Testis and its Appendages - Chapman, R. H. (1972)
In a survey of 101 cases with an index diagnosis of torsion of the testis or its appendage, there were 86 instances of torsion of the testis and 14 of torsion of the hydatid of Morgagni. In 38 of the patients with testicular torsion there were one or more “warning” attacks of pain and swelling, due to torsion which became spontaneously untwisted. In 19 cases operative fixation was performed because of this warning history, and all the testes were preserved. In the other 19 the testes were not explored until the patient came in with a severe “classical” episode of torsion: seven of these testicles were lost from gangrene or delayed atrophy. In 31 cases torsion resulted in failure to save the testis. Of these, 20 were misdiagnosed and treated initially as epididymo-orchitis, despite there being no evidence of a urinary tract infection. There is no excuse for not exploring any actuely inflammed testicle which is unaccompanied by definite evidence of urinary or urethral infection.